PENINGKATAN KUANTITAS DAN KUALITAS PERTANYAAN PESERTA DIDIK MELALUI PENERAPAN MODEL PROJECT BASED LEARNING PADA PEMBELAJARAN BIOLOGI - Fadhilla Cahya Alifa; Sri Widoretno; Joko Ariyanto (Universitas Sebelas Maret, 2019)
This research aimed to enhance quantity and quality of student’s questions in biology at grade X MIPA 1 of SMAN 7 Surakarta academic year 2014/2015 through the implementation of project based learning. This research was a Classroom Action Research which consisting of planning, acting, observing, and reflecting. Subject of the research was grade X MIPA 1 of SMAN 7 Surakarta academic year 2014/2015, consisting of 28 students. Data were collected through observation, interview, and video recording, then its collected based on revised Bloom’s Taxonomy. Data were analyzed describe qualitatively. Data were validated using triangulation methods. Research procedure using spiral model.The result of the research showed that quantity and quality of student’s questions enhance from Preaction, Cycle I, and Cycle II. Quantity of student’s questions enhance from 24 to 180 questions. Quality of students’ questions enhanced from the factual, conceptual, and procedural dimension at the C1, C2, and C3 become the factual, conceptual, procedural and metacognition dimension at the C1, C2, C3, C4, C5, and C6. Based on the data analysis result, it can be concluded that the implementation of project based learning is able to enhance quantity and quality of student’s questions in biology at grade X MIPA 1 of SMAN 7 Surakarta academic year 2014/2015.